Ecological Landscape Modeling: The General Application of an Existing Simulation Framework - H. Carl Fitz (EDIS)
SL321, an 8-page illustrated fact sheet by H. Carl Fitz, is an overview of an existing, generalized model framework that synthesizes integrated ecosystem dynamics within large spatial domains and across decadal ecological time scales. Includes references. Published by the UF Department of Soil and Water Science, June 2010.